THE PREVALENCE OF TUBERCULOSIS POSES A SERIOUS CHALLENGE TO PUBLIC HEALTH (International journal of medical sciences, 2025)
Tuberculosis (TB) persists as a significant global health burden, despite substantial advances in diagnostic methodologies and therapeutic regimens.[1] The disease’s epidemiological resilience is driven by a combination of biological, clinical, and socio-environmental determinants. Latent Mycobacterium tuberculosis infection remains widespread, serving as a continuous reservoir for active disease, particularly among individuals with compromised immune function. Moreover, the increasing prevalence of multidrug-resistant (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) presents a critical challenge to existing treatment frameworks and poses a threat to global TB control strategies[2] Transmission occurs primarily via aerosolized droplets, with clinical manifestations typically including chronic cough, fever, weight loss, and night sweats. Effective TB control mandates integrated approaches encompassing early and accurate detection, strict adherence to prolonged pharmacological therapy, sustained vaccination programs, and targeted interventions addressing structural determinants such as poverty, overcrowding, and limited healthcare access. Strengthening health systems and enhancing population-level awareness are essential to mitigating transmission dynamics and reducing TB-associated morbidity and mortality.[4]